REFORMING INDONESIA'S AGRICULTURAL LEGAL SYSTEM: EMPOWERING FAMILY-BASED FARMERS FOR SUSTAINABLE DEVELOPMENT AND SOCIAL SECURITY INTEGRATION - Andjarwati, Any (Masalah-Masalah Hukum, 2025)
Agriculture plays a vital role in sustaining the economy and livelihoods, particularly in developing countries. In Indonesia, the agricultural sector faces several challenges, including widespread farmer poverty, low incomes, climate change impacts, and inadequate agricultural insurance. These issues underscore the need for a reformed agricultural legal system focused on empowering family-based farmers and ensuring sustainable agricultural practices. This research examines the existing agricultural legal framework in Indonesia, identifying the limitations in farmer welfare and social protection mechanisms. The study emphasizes the importance of transforming informal agricultural employment into formalized agricultural work, aligning with the Sustainable Development Goals (SDGs) of eradicating poverty and hunger. It also highlights the need for a comprehensive Agricultural Legal System that guarantees social security, implements agricultural insurance, and provides a legal foundation for family-based agricultural operations. The findings suggest that a paradigm shift toward recognizing farmers as individual legal subjects, alongside policy reforms in agricultural insurance and social security systems, is crucial for improving the livelihoods of farmers and achieving sustainable agricultural development. This research proposes the establishment of a dedicated Farmer Social Security system, ensuring health, pension, and accident coverage, to promote farmer welfare and facilitate the transition to a formal agricultural economy.